Analyzing the Impact of store Atmosphere and Location on Consumer Purchase Intention: A Case Study at Opsal Plaza (Sejahtera) Palopo - Sasmita, Indra; Silvana, Silvana; Leni, Leni; Nurjannah, Nurjannah; Mahmut, Cici (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to analyze the influence of store atmosphere and location on consumer purchase intention at Opsal Plaza (Sejahtera) Palopo. In the face of growing competition in the modern retail sector, understanding the factors that drive consumer purchasing decisions is increasingly crucial. The research employs a quantitative approach using multiple linear regression to analyze data collected from 30 respondents through questionnaires, observations, and interviews. The results indicate that both store atmosphere and location have a significant partial and simultaneous effect on consumer purchase intention. Among the two, store atmosphere shows a more dominant influence, as reflected in the higher regression coefficient. These findings suggest that a combination of a pleasant store environment and accessible location enhances the consumer shopping experience and increases the likelihood of purchase. This study provides valuable insights for retail management in developing more effective, consumer-centered marketing strategies.